Mathematical Communication and Students' Epistemological Beliefs of Linear Systems with Three Variables - Mastuti, Ajeng Gelora; Kaliky, Syafruddin; Arman, Juanda (Universitas Muhammadiyah Mataram, 2022)
Epistemological beliefs simultaneously affect mathematical communication skills. The higher the epistemological beliefs of a person's ability to formulate concepts, convey ideas, and hone ideas to convince others, the more mathematical communication skills will increase. This qualitative study uses three variables to describe mathematical communication and students' epistemological beliefs on linear system material. The subjects in this study were students who had epistemological beliefs from the test results, and students who were taken were students who were able to meet the indicators of epistemological confidence. Data collection techniques are tests, interviews and documentation. The results of this study indicate that students have beliefs that do not change or remain in solving test questions. The method used is more consistent with the way of solving, which according to students, is easy to do, able to solve problems by multiplying exercises and repeating what has been learned, solving problems by following the steps and methods of completion taught by the teacher, students can estimate answers or problem solving because of problems The subject obtained is obtained from experience and observations in everyday life.